Analisis Efisiensi Saluran Pemasaran Buah Jeruk Di Desa Lau Riman Kabupaten Tanah Karo - Warsani Purnamasari; Dhian Rosalina; Isnaniah Laili KS; Desy Astrid Anindya (Fakultas Ekonomi Universitas Kadiri, 2022)
Lau Riman Village is a citrus fruit plantation area in Tanah Karo Regency. Oranges are the leading commodity in this village, so the marketing aspect is an important part of selling and earning profits. This study aimed to identify an efficient and profitable distribution channel pattern for citrus fruit farmers in Lau Riman Village, Tanah Karo Regency. This research is quantitative descriptive research. The number of respondents in this study were eighty-eight citrus farmers in Lau Riman Village. Analysis of the data used is the farmer share approach, marketing margin, and market efficiency. The results of this study there are three marketing channels, hereinafter referred to as channels I, II, III. Efficient farmer share only exists in channel I, which only involves retailers as marketing institutions. The highest margin is in marketing channel III where marketing agencies reach out to markets outside North Sumatra, and the efficiency of marketing channels shows that the three channels used by citrus fruit farmers are less efficient